2012
DOI: 10.1111/j.1365-2265.2011.04315.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum sclerostin levels were positively correlated with fat mass and bone mineral density in Central South Chinese postmenopausal women

Abstract: This study showed that in central south Chinese postmenopausal women, serum sclerostin is lower in women with osteoporosis than without. Serum sclerostin is positively correlated with fat mass and BMD for the whole body, lumbar spine and hip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 23 publications
(86 reference statements)
4
47
4
1
Order By: Relevance
“…The association we observed between sclerostin levels and height in the multivariable model is discrepant compared to the results observed in the literature [27,34,35,36,37]. The association with height, and thus to bone length, could be however logical from a physiological point of view as the protein is principally secreted by osteocytes.…”
Section: Discussioncontrasting
confidence: 56%
“…The association we observed between sclerostin levels and height in the multivariable model is discrepant compared to the results observed in the literature [27,34,35,36,37]. The association with height, and thus to bone length, could be however logical from a physiological point of view as the protein is principally secreted by osteocytes.…”
Section: Discussioncontrasting
confidence: 56%
“…(18,23) Recently, similar to the findings of the present study, we found significant correlations between serum sclerostin and BMD for lumbar spine (L 1 -L 4 ) and femur neck in postmenopausal women, but such correlations disappeared after adjustment for age and BMI. (18) These findings contrast with that reported by some studies: Modder and colleagues (23) (for postmenopausal women, although no information was given on the mean of the age of women studied), Sheng and colleagues (35) (for postmenopausal women; women with and without osteoporosis were included in the analysis), and Amrein and colleagues (30) (for postmenopausal women and men; both included in the analysis), but concurrent with what was reported by Mirza and colleagues (36) in postmenopausal women. Such differences are mostly driven by variations in the selection criteria of women studied, health status, (35) inclusion of men in the analysis, (30) and the mean age of the group examined.…”
Section: Discussionmentioning
confidence: 71%
“…(18) These findings contrast with that reported by some studies: Modder and colleagues (23) (for postmenopausal women, although no information was given on the mean of the age of women studied), Sheng and colleagues (35) (for postmenopausal women; women with and without osteoporosis were included in the analysis), and Amrein and colleagues (30) (for postmenopausal women and men; both included in the analysis), but concurrent with what was reported by Mirza and colleagues (36) in postmenopausal women. Such differences are mostly driven by variations in the selection criteria of women studied, health status, (35) inclusion of men in the analysis, (30) and the mean age of the group examined. (23) It is also possible that environmental or lifestyle and/or genetic influences on bone mass, and consequently serum sclerostin, not accounted for in the current cohort, to be taken into consideration to explain the observed relation between serum sclerostin and BMD values among postmenopausal women studied.…”
Section: Discussionmentioning
confidence: 71%
“…[6,7] However, several reports have failed to find these expected results. Sheng et al [8] found low sclerostin levels in osteoporotic women; Faje et al [9] found no changes in sclerostin levels in girls affected by anorexia nervosa; García-Martín et al [10] also report lower sclerostin lev-els in type 2 diabetic patients with osteoporosis. In a recent report we showed that sclerostin levels, although higher among alcoholics, were related to liver function derangement instead to bone mineral density (BMD), although a relationship was observed with decreased markers of bone synthesis and increased markers of bone breakdown.…”
Section: Introductionmentioning
confidence: 99%